A SOCIO-ECONOMIC ANALYSIS OF OLD AGE POPULATION BIHAR - RAVI SHANKAR KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
The process of urbanization, which is associated with high fertility and rapid population increase in India and in an impoverished state like Bihar, is heavily influenced by the forces that regulate the growth and mobility of the people, also known as population dynamics. This is because urbanisation is associated with high fertility and rapid population increase in India. In addition to shifting people from rural areas to urban settings, the process of urbanisation also brings about changes to the entire social structure as well as demographic characteristics. These characteristics include occupation, culture, way of life, and general behaviour. The majority of the data bases that were utilised come from the census as well as the sample registration system that was made available by the registrar general of India. Both of these systems were published by the Indian government. The socioeconomic profile has addressed a variety of subjects, some of which include the following: the literacy rate of the elderly; their educational level; their regional pattern; their marriage status; widowhood; the old age dependency ratio; the labour participation rate; and their regional pattern. Other factors, such as their regional pattern, have also been covered for the profile.